Multi-Institutional Experience with FOLFIRINOX in Pancreatic Adenocarcinoma - Peddi, Parvin Fatheddin; Lubner, Sam; McWilliams, Robert; Tan, Benjamin R; Picus, Joel; Sorscher, Steven M; Suresh, Rama; Lockhart, A Craig; Wang, Jian; Menias, Christine; Gao, Feng; Linehan, David; et al. (JOP. Journal of the Pancreas, 2012)
Context Combination chemotherapy with FOLFIRINOX (oxaliplatin, irinotecan, fluorouracil, and leucovorin) was shown to be effective in a large phase III trial. Objective The purpose of this study was to examine the tolerance and effectiveness of FOLFIRINOX as practiced outside of the confines of a clinical trial and to document any dose modifications used by practicing oncologists. Methods Data on patients with all stages of pancreatic adenocarcinoma treated with FOLFIRINOX at three institutions was analyzed for efficacy, tolerance, and use of any dose modifications. Results Total of 61 patients was included in this review. Median age was 58 years (range: 37 to 72 years), 33 were male (54.1%) and majority had ECOG performance of 0 or 1 (86.9%, 53 patients). Thirty-eight (62.3%) had metastatic disease, while 23 (37.7%) were treated for locally advanced or borderline resectable disease. Patients were treated with a median number of four cycles of FOLFIRINOX, with dose modifications in 58.3% (176/302) of all cycles. Ten patients had stable disease (16.4%), four had a partial response (6.6%) while eight had progressive disease (13.1%) on best imaging following therapy. Median progression-free survival and overall survival were 7.5 months and 13.5 months, respectively. The most common grade 3-4 adverse event was neutropenia at 19.7% (12 cases), with 4.9% (3 cases) rate of febrile neutropenia. Twenty-one patients (34.4%) were hospitalized as a result of therapy but there were no therapy-related deaths. Twenty-three (37.7%) had therapy eventually discontinued as a result of adverse events. Conclusion Despite substantial rates of adverse events and use of dose modifications, FOLFIRINOX was found to be clinically effective in both metastatic and non-metastatic patients. Regimen toxicity did not detract from overall response and survival. Image: Overall and progression free survival in all patients and subset with metastatic disease.